Synthesis, Characterization, Protonation and Electrochemical Investigation of Diiron Tetracarbonyl Complex as a Model of [FeFe]-Hydrogenase - Xiao, Zhiyin; Li, Zhimei; Qian, Guifen; Long, Li (Asian Journal of Chemistry, 2011)
As structural and functional relevancy to the active site in [FeFe]-hydrogenase, the diiron carbonyl complexes attracted our attentions. A phosphine-substituted complex (2) containing a pyridine group was synthesized by reaction of a diiron pentacarbonyl model complex (1) with triphenyl phosphine. Complex 2 was fully characterized by using FT-IR, NMR spectroscopies as well as elemental analysis. Protonation of the complex and electrochemical behaviours in the absence and presence of a strong acid were also investigated. The results showed that the bridging hydride was obtained and it catalyzed proton reduced at a rather positive potential, which was only about 0.15 V negative to the estimated standard potential.